2015
DOI: 10.1186/s12891-015-0533-2
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect on pain and function of neurophysiological education and sensorimotor retraining compared to usual physiotherapy in patients with chronic or recurrent non-specific low back pain, a pilot randomized controlled trial

Abstract: BackgroundNon-specific chronic low back pain (NSCLBP) is a major health problem. Identification of subgroups and appropriate treatment regimen was proposed as a key priority by the Cochrane Back Review Group. We developed a multimodal treatment (MMT) for patients with moderate to severe disability and medium risk of poor outcome. MMT includes a) neurophysiological education on the perception of pain to decrease self-limitation due to catastrophizing believes about the nature of NSCLBP, b) sensory training of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
113
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(120 citation statements)
references
References 39 publications
2
113
0
5
Order By: Relevance
“…This resulted in 42 records to be assessed as full text for eligibility. Eventually, 7 RCTs (12 articles) met predefined eligibility criteria and were included in the systematic review …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This resulted in 42 records to be assessed as full text for eligibility. Eventually, 7 RCTs (12 articles) met predefined eligibility criteria and were included in the systematic review …”
Section: Resultsmentioning
confidence: 99%
“…One study reported a relatively low fear‐avoidance beliefs score (Fear‐Avoidance Beliefs Questionnaire [FABQ] physical activity score < 14), while 3 studies reported increased fear‐avoidance beliefs (FABQ physical activity score > 14) or kinesiophobia (Tampa Scale for Kinesiophobia [TSK] score ≥ 37) . Wälti et al did not report on subscales specifically but reported an FABQ total score for which no cut‐off values are available. Total scores included 23.93 ± 11.58 (BPS intervention) and 25.92 ± 12.28 (control group).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations